(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Behavioural finance seeks to understand how cognitive biases and emotional variables influence investing decisions. The purpose of this study article is to better understand numerous cognitive biases that impact investor behaviour & contribute to subprime investing decisions. The study also investigates how emotions like fear and greed influence investment decisions. This research article presents an overview of key ideas and theories in field of behavioral finance, such as prospect theory, loss aversion, overconfidence, and herding behavior. It also explores the results' ramifications for investors, financial experts, and legislators, as well as ways for overcoming subconscious prejudices and making more sound financial decisions.